Charakterystyka usług dostępnych w handlu mobilnym (m-commerce) - Łysik, Łukasz (The Characteristic of Mobile Commerce Transactions, 2007)
This article is focused on mobile electronic commerce, also known as m-commerce. It was the rapid growth of ICT that enabled business transaction being conducted through mobile channels. The main aim of this article is to present the foundations but also to present what were the reasons of emergence of phenomenon called m-commerce. Main types of transactions being conducted and application of mobile technology in contemporary commerce are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 138-148